Changes of Soil Aggregate on Degraded Jasinga Ultisols by Soil Tillage and Organic Matter Practices - NENENG LAILA NURIDA; UNDANG KURNIA (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2009)
Soil aggregate is soil characteristics which is sensitive to change due to soil tillage. Organic matter practices and soil tillage difference have an important role in determining the quality and quantity of soil aggregate. The objective of this research is to study the quality changes of soil aggregation on Ultisols Jasinga degraded by various soil tillage and organic matter practices. This research was carried out at Jasinga Village, Jasinga Sub District, Bogor District in 2003 planting season (PS). The randomized block design with three replications was used. The Main plot was artificial desurfacing which consisted of three treatments, i.e: non-artificial desurfacing, 5 cm depth of artificial desurfacing, and10 cm depth of artificial desurfacing, whereas sub plot treatments were soil tillage and soil rehabilitation with Mucuna sp. (tillage+Mucuna sp.), no soil tillage and without rehabilitation (no tillage without Mucuna sp.), soil tillage without rehabilitation (tillage without Mucuna sp.), and no soil tillage with rehabilitation (no tillage+Mucuna sp.). The result of this research showed that periodic application of fresh organic matters was able to maintain the quality of macroaggregate on eroded soil (0.36-15.47 cm). Minimum soil tillage application and continuos organic matter practices (>21 t ha-1 year-1) are soil conservation technique that has been able to maintain soil aggregate, even without rehabilitation with Mucuna sp. Various organic matters (Mucuna sp., plant waste, and flemingia) are needed to be applied periodically to maintain the quality of soil aggregate.